PET Study Examining Pharmacokinetics, Detection and Likeability, and Dopamine Transporter Receptor Occupancy of Short- and Long-Acting Oral Methylphenidate - Spencer, Thomas J.; Biederman, Joseph; E. Ciccone, Patrick; Madras, Bertha K.; Dougherty, Darin D.; Bonab, Ali A.; Livni, Elijahu; Parasrampuria, Dolly A.; Fischman, Alan J. (The American journal of psychiatry, 2006)
OBJECTIVE: The abuse potential of methylphenidate has been related to the drug's capacity to produce a rapid onset of blockade of the presynaptic dopamine transporter in the brain. An oral once-a-day osmotic controlled-release formulation of methylphenidate produces a more gradual rise in plasma methylphenidate concentration, compared with immediate-release methylphenidate. The authors hypothesized that osmotic-release methylphenidate would also produce a slower onset of blockade of the presynaptic dopamine transporter and would be associated with a lower risk for detection and likeability, compared to immediate-release methylphenidate. METHOD: Twelve healthy adults were randomly assigned to receive single doses of immediate-release methylphenidate or osmotic-release methylphenidate. Doses predicted to produce equivalent maximum concentration (Cmax) values were selected (40 mg of immediate-release methylphenidate and 90 mg of osmotic-release methylphenidate). Plasma d-methylphenidate levels and responses to detection likeability questionnaire items were obtained hourly for 10 hours after administration of methylphenidate on two separate occasions for each subject. Dopamine transporter receptor occupancies were measured at hours 1, 3, 5, and 7 by using a carbon-11-labeled imaging agent (Altropane) and positron emission tomography. RESULTS: Despite similar Cmax values for both formulations, osmotic-release methylphenidate was associated with a longer time to maximum concentration, longer time to maximum CNS dopamine transporter occupancy, and no detection likeability, compared with immediate-release methylphenidate. CONCLUSIONS: The findings suggest that the abuse potential of oral methylphenidate is strongly influenced by the rate of delivery and not solely by the magnitude of plasma concentration or brain transporter occupancy. These results advance understanding of the underlying central effects of methylphenidate in humans and identify a potentially less abusable methylphenidate formulation.